Fibrewise Pairwise bi-Separation Axioms - Yousif, Y Y; Hussain, L A (Al-Nahrain Journal of Science, 2018)
The main idea of this research is to consider fibrewise pairwise versions of the more important separation axioms of ordinary bitopology named fibrewise pairwise -  spaces, fibrewise pairwise  -  spaces, fibrewise pairwise -  spaces, fibrewise pairwise -Hausdorff spaces, fibrewise pairwise functionally -Hausdorff spaces, fibrewise pairwise -regular spaces, fibrewise pairwise completely -regular spaces, fibrewise pairwise -normal spaces and fibrewise pairwise functionally -normal spaces. In addition we offer some results concerning it.2010 MSC: 55R70, 54C05,54C08,54C10, 54D10, 54D15.